PENGARUH KONSENTRASI KOLKISIN TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN KEDELAI HITAM VARIETAS DETAM 2 (Glycine soja (L.) Merr) - Noer Afny Mulyati Sodiq; Fathurrahman; Saripah Ulpah (Ekoagrotrop, 2023)
Research entitled The Effect of Colchicine Concentration on the Growth and Production of Black Soybean Plants of the Detam 2 Variety (Glycine soja (L) Merr). The aim of this research was to determine the concentration of LD47, as well as the effect of colchicine concentration on the growth and yield of black soybean plants of the Detam 2 variety (Glycine soja (L) Merr). The research was carried out at the Air Dingin experimental garden, Faculty of Agriculture, Universitas Islam Riau. The research period was carried out for six months from January to June 2023. The research carried out consisted of II stages. Phase I research was to determine the concentration of colchicine LD47 (Lethal Dose 47%). The treatment concentrations are: K0= 0 ppm, K1= 500 ppm, K2= 1000 ppm, K3= 500 ppm, K4= 2000 ppm, K5= 2500 ppm, K6= 3000 ppm, K7= 3500 ppm. Phase II research was carried out by inducing colchicine mutations using control and LD47. Phase II research was carried out to determine the effect on growth and production in control and treatment samples that had been mutated with LD47 concentrations. Phase I research showed the sensitivity of black soybean plants with a survival percentage of 47%. It can be seen that the LD50 concentration obtained was 3599 ppm and the concentration used for phase II was LD47 colchicine concentration of 3500 ppm. The effect of colchicine LD47 had a significant effect on the parameters of petiole length, number of branches, widest leaf area, stem diameter, flowering age, number of pods per plant and dry seed weight per plant. The effect of colchicine LD47 had no significant effect on the parameters of plant height, node or node length, percentage of pithy pods, fruit stalk length and weight of 100 dry seeds.